Whole Prostate Volume and Shape Changes with the Use of an Inflatable and Flexible Endorectal Coil. (13th October 2014) - Osman, Murat; Shebel, Haytham; Sankineni, Sandeep; Bernardo, Marcelino L.; Daar, Dagane; Wood, Bradford J.; Pinto, Peter A.; Choyke, Peter L.; Turkbey, Baris; Agarwal, Harsh K.
Abstract : Purpose. To determine to what extent an inflatable endorectal coil (ERC) affects whole prostate (WP) volume and shape during prostate MRI. Materials and Methods. 79 consecutive patients underwent T2W MRI at 3T first with a 6-channel surface coil and then with the combination of a 16-channel surface coil and ERC in the same imaging session. WP volume was assessed by manually contouring the prostate in each T2W axial slice. PSA density was also calculated. The maximum anterior-posterior (AP), left-right (LR), and craniocaudal (CC) prostate dimensions were measured. Changes in WP prostate volume, PSA density, and prostate dimensions were then evaluated. Results. In 79 patients, use of an ERC yielded no significant change in whole prostate volume (0.6 ± 5.7 %, P = 0.270 ) and PSA density (- 0.2 ± 5.6 %, P = 0.768 ). However, use of an ERC significantly decreased the AP dimension of the prostate by - 8.6 ± 7.8 % (P < 0.001 ), increased LR dimension by 4.5 ± 5.8 % (P < 0.001 ), and increased the CC dimension by 8.8 ± 6.9 % (P < 0.001 ). Conclusion. Use of an ERC in prostate MRI results in the shape deformation of the prostate gland with no significant change in the volume of the prostate measured on T2W MRI. Therefore, WP volumes calculated on ERC MRI can be reliably used in clinical workflow.